Effect of Fair Value Measurement on the Share Price of Listed Deposit Money Banks in Nigeria - Alkali, Umar Hassan; Bagudo, M. M.; Aliyu, Abdullahi A. (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
This study examined the effect of fair value accounting on share price of listed deposit money banks in Nigeria from 2016 to 2022. the data used was obtained from the annual reports of the banks. OLS regression was employed in the analysis of the data. The results from the regression analysis show that earnings per share, fair value hierarchy, fair value through other comprehensive income have significant effect on the value relevance of listed deposit money banks in Nigeria. The study concludes that earnings per share is an important variable investor’s pays attention to when making investment decision. In addition, the study concludes that banks which discloses information regarding fair value hierarchy will attract investors and this will result in a corresponding increase in share price. Furthermore, the study concludes that investors pay close and more attention to other comprehensive income value. And finally, the study concludes that fair value through other comprehensive income have an effect on the share price of listed deposit money banks in Nigeria. The study therefore, recommends among others that management of listed deposit money banks in Nigeria should ensure that information using fair value are disclosed since its disclosure have an effect on share price. The study also recommends that regulatory bodies should establish an evaluation system to monitor adequate discourse of fair value information.